The Role Of Women Self Defense Of Silat (Wsd's) As An Effort To Prevent Cases Of Violence - Siti Hanifah; Berliana Rahely; Nina Sutresna (JUARA : Jurnal Olahraga, 2023)
Every year, violence against women increases because women are always seen as weaker. So, this research aims to protect women from criminal threats through Women Self-Defense of Silat (WSDs). Then this research uses the descriptive analysis method, a literature study supported by distributing questionnaires to respondents. After the research data was collected, the results obtained in this study were the inability of women to protect themselves when they became victims of violence and crime or other things. WSDs emerged as special martial arts training facilities for women. So it is hoped that WSD's martial arts can become a tool to make it easier for women to practice through WSD's e-books.